Evaluation of Metabolic Syndrome and Related Factors in Children Affected by Acute Lymphoblastic Leukemia - Zareifar, Soheila; Haghpanah, Sezaneh; Shorafa, Eslam; Shakibazad, Nader; Karamizadeh, Zohreh (Indian Journal of Medical and Paediatric Oncology, 2017)
Introduction: Obesity is among the medical problems in survivors of childhood acute lymphoblastic leukemia (ALL). These patients are at risk of metabolic syndrome (MS). The present study aimed to follow the patients with ALL regarding the incidence of MS. Patients and Methods: This study was conducted on all patients who referred to the oncology clinic from July 2012 to July 2013. The exclusion criteria of the study were ALL relapse, secondary malignancy, hypothyroidism, Down syndrome, and below 2 years of age. ALL had to be diagnosed at least 12 months before enrollment into this study. MS was assessed by serum triglyceride, cholesterol, fasting blood sugar, leptin, and insulin levels. Besides, body mass index (BMI) and blood pressure (BP) were measured at diagnosis and at the last visit. Results: This study was conducted on 53 patients (male = 35, female = 18). At the end of the study, 13 patients (24.53%) were overweight compared to 3 patients at diagnosis (P = 0.04). The mean blood leptin level was higher in overweight patients compared to the others (P = 0.001). MS was detected in 21 patients (39.6%), including 12 males and 9 females. In addition, the BMI Z- score significantly increased over the study period (P = 0.001). Conclusions: Being overweight is a complication of ALL treatment, which is associated with elevated blood leptin level and BMI Z- score. Therefore, MS criteria, such as BP, weight, and serum triglyceride level, should be taken into account in each visit.
Keywords: Acute lymphoblastic leukemia; body mass index; leptin; metabolic syndrome; overweight